Sleep and behavioral disturbances induced by epilepsy: Protective effect of Gabapentin - Ayala Guerrero, Fructuoso; Mexicano Medina, Graciela; Guerrero, Angel; Gutiérrez Chávez, Carlos Alberto; Lazo Sánchez, Legna Alejandra; Mateos Salgado, Erik Leonardo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
Numerous sleep disturbances induced by nocturnal epilepsy have been reported. Gabapentin (GBP) is used as an adjuvant or as a monotherapeutic treatment as it induces significant improvement in patients with partial or secondaryly widespread focal seizures. In experimental animal models of epilepsy with pentilenetetrazole (PTZ), GBP protects against the generated seizures. The objective of this work was to investigate its effectiveness in protecting against motor and sleep disturbances caused by seizures. Polygraphic studies were conducted in male wistar rats, separated into 4 groups. After administration of saline solution, a check record was carried out on each group. Subsequently, one group received 50 mg/kg of PTZ, while the other three groups received 15, 30 or 60 mg/kg GBP, 30 minutes prior to PTZ administration. After administration of PTZ, electrophysiological and behavioral manifestations characterizing seizures were observed. In addition, surveillance states were significantly altered, increasing the amount of wakefulness, while sleep was inhibited over a period of time. The administration of increasing doses of GBP tended to inhibit the presence of abnormal motor behaviors, facilitating the presence of sleep.